¬¬Perancangan Interior Pusat Informasi Sepak Bola Gelora Bung Tomo di Surabaya - Andreas Andika Jaya (Intra, 2015)
Interior design Football Information Center in Surabaya This raised the issue of the lack of space to accommodate about information the basic theories of football in Surabaya.Interior design Football Information Center in Surabaya is a public building that serves as the source of all information about football. The design aims to create football information center that does not exist in Surabaya as a means of knowledge of the history of football soccer theory, tactics, player positions, football techniques, how to exercise that right, according to standards of FIFA football regulations, as well as the treatment and healing of injury, and as container which directly brings visitors who have a penchant football. Football information center has a main facility area football information, and support facilities such as mini theathre, press conference rooms, cafes, and shops. All these facilities can be enjoyed by a wide range of backgrounds and ages.